Degradation of sulfamethoxazole by UV, UV/H2O2 and UV/persulfate (PDS): Formation of oxidation products and effect of bicarbonate. (1st July 2017) - Yang, Yi; Lu, Xinglin; Jiang, Jin; Ma, Jun; Liu, Guanqi; Cao, Ying; Liu, Weili; Li, Juan; Pang, Suyan; Kong, Xiujuan; Luo, Congwei
Abstract: The frequent detection of sulfamethoxazole (SMX) in wastewater and surface waters gives rise of concerns about their ecotoxicological effects and potential risks to induce antibacterial resistant genes. UV/hydrogen peroxide (UV/H2 O2 ) and UV/persulfate (UV/PDS) advanced oxidation processes have been demonstrated to be effective for the elimination of SMX, but there is still a need for a deeper understanding of product formations. In this study, we identified and compared the transformation products of SMX in UV, UV/H2 O2 and UV/PDS processes. Because of the electrophilic nature of SO4 -, the second-order rate constant for the reaction of sulfate radical (SO4 - ) with the anionic form of SMX was higher than that with the neutral form, while hydroxyl radical (OH) exhibited comparable reactivity to both forms. The direct photolysis of SMX predominately occurred through cleavage of the NS bond, rearrangement of the isoxazole ring, and hydroxylation mechanisms. Hydroxylation was the dominant pathway for the reaction of OH with SMX. SO4 - favored attack on NH2 group of SMX to generate a nitro derivative and dimeric products. The presence of bicarbonate in UV/H2 O2 inhibited the formation of hydroxylated products, but promoted the formation of the nitro derivative and the dimeric products. In UV/PDS, bicarbonate increased the formation of the nitro derivative and the dimeric products, but decreased the formation of the hydroxylated dimeric products. The different effect of bicarbonate on transformation products in UV/H2 O2 vs. UV/PDS suggested that carbonate radical (CO3 - ) oxidized SMX through the electron transfer mechanism similar to SO4 - but with less oxidation capacity. Additionally, SO4 - and CO3 - exhibited higher reactivity to the oxazole ring than the isoxazole ring of SMX. Ecotoxicity of transformation products was estimated by ECOSAR program based on the quantitative structure-activity relationship analysis as well as by experiments using Vibrio fischeri, and these results indicated that the oxidation of SO4 - or CO3 - with SMX generated more toxic products than those of OH. Graphical abstract: Highlights: Reaction rate constants of OH and SO4 - with sulfamethoxazole were determined. Hydroxylated products was predominant in UV/H2 O2 . SO4 - favored attack on NH2 group to form a nitro derivative and dimeric products. CO3 - enhanced oxidation of NH2 group. SO4 - or CO3 - oxidation generated more toxic products than OH oxidation.